Gifts of the Spirit and the Spirit as Gift?: A Reformed Perspective - Marais, Nadia (Pneuma: The Journal of the Society for Pentecostal Studies, 2019)
The article focuses on the gift-giving work of the Holy Spirit. It mentions that the distinction between Pentecostal and Catholic perspectives on the gifts of the Holy Spirit is a matter of theological emphasis; and also mentions that the Charisms are portrayed as part of the ongoing work of sanctification.
Paid
Keywords: CATHOLICS; HOLY Spirit; PENTECOSTALS; SANCTIFICATION; SPIRITUAL gifts